Status for miljørigtigt idrætsbyggeri i Danmark - Mortensen, Bente (Forum for Idræt, 2004)
The current state of play for the construction of environmentally friendly sports facilities in Denmark No attention is paid to environmental concerns when new facilities for sports are constructed. This article charts the degree to which environmental concerns are brought into play in the planning and maintenance of sports facilities in Denmark. Taking a pair of actual cases as a starting point, the author presents the current state of play as regards the efforts made in this area by sporting bodies, organisations, the authorities and advisers.